Physical and chemical treatment of poultry feather from the slaughter-house - Mézes, Lili (Acta Agraria Debreceniensis, 2010)
The 15-20% of the by-products of meat – and poultry industry – that unsuitable for human consumption – contains keratin. The slaughter technology of poultry produces large amount of poultry feather with 50-70% moisture content. This means more million tons annually worldwide (Williams et al., 1991; Hegedűs et al., 1998). The keratin content of feather can be difficulty digested, so physical, chemical and/or biological pretreatment is needed in practice, which has to be set according to the utilization method.Our applied treatments were based on biogas production, which is a possible utilization method. In the IFA (TULLN) Environmental Biotechnology Institute the feather was homogenized, and – according to the previous examinations – the most effective 1:2 feather-distilled water ratio or 1% NaOH-solution was used, and then treated with microwave (70, 130, 160 °C) during 1 hour time period. DM% and oDM% content was analyzed in the original samples, and the pH, Carbon-, Nitrogen-content in the output, too. Based on the received correlation coefficients (R) and related significance values (Sig.) I concluded, that the C-, N-content and the pH values weren’t influenced by any of the additives. The temperatureaffected all three tested factors. The temperature showed a strong coherency with the N-content and the pH value when distilled water was used and weak-medium coherency with the Carboncontent. With NaOH-solution treatment the temperature gave strong coherency with the C- and N-content, as well as medium coherency with the pH. Our objective was to determine the method with effectively the pre-treating of poultry feather for biogas production or composting and to prepare of the treated samples for N and C analyzing. Our next aims will be the elaboration of the technological parameters of heat pre-treatment and microbial digestion of poultry feather for biogas production.